Organ sparing of linac‐based targeted marrow irradiation over total body irradiation. Issue 11 (11th October 2019) - Warrell, Gregory R.; Colussi, Valdir C.; Swanson, Wayne L.; Caimi, Paolo F.; Mansur, David B.; de Lima, Marcos J. G.; Pereira, Gisele C.
Abstract : Purpose: Targeted marrow irradiation (TMI) is an alternative conditioning regimen to total body irradiation (TBI) before bone marrow transplantation in hematologic malignancies. Intensity‐modulation methods of external beam radiation therapy are intended to permit significant organ sparing while maintaining adequate target coverage, improving the therapeutic ratio. This study directly compares the dose distributions to targets and organs at risk from TMI and TBI, both modalities conducted by general‐use medical linacs at our institution. Methods: TMI treatments were planned for 10 patients using multi‐isocentric feathered volumetric arc therapy (VMAT) plans, delivered by 6 MV photon beams of Elekta Synergy linacs. The computed tomography (CT) datasets used to obtain these plans were also used to generate dose distributions of TBI treatments given in the AP/PA extended‐field method. We compared dose distributions normalized to the same prescription for both plan types. The generalized equivalent uniform dose (gEUD) of Niemierko for organs and target volumes was used to quantify effective whole structure dose and dose savings. Results: For the clinical target volume (CTV), no significant differences were found in mean dose or gEUD, although the radical dose homogeneity index (minimum dose divided by maximum dose) was 31.7% lower ( P  = 0.002) and the standard deviation of dose was 28.0% greater ( P =  0.027) in the TMI plans than in the TBI plans. For the TMI plans, gEUD to the lungs, brain, kidneys, and liver was significantly lower ( P  < 0.001) by 47.8%, 33.3%, 55.4%, and 51.0%, respectively. Conclusion: TMI is capable of maintaining CTV coverage as compared to that achieved in TBI, while significantly sparing organs at risk. Improvement on sparing organs at risk permits a higher prescribed dose to the target or the maximum number of times marrow conditioning may be delivered to a patient while maintaining similar typical tissue complication rates.